Використання моделі прийняття рішень в умовах невизначеності та ризику в інформаційній системі планування реклами спеціалізованих ножів - Шкурат, Д. І. (ХНУРЕ, 2023)
This article discusses the development of an IS for planning the advertising of specialized knives using a decision-making model in conditions of uncertainty and risk. The article highlights the importance of effective advertising planning for businesses in the knife industry and the challenges associated with decision-making. The use of a decision-making model that takes into account multiple factors such as market trends, customer preferences, and advertising costs is proposed. The development of the IS and its key features such as data collection, analysis, and visualization is described. The article concludes by emphasizing the significance of incorporating decision-making models and IS in advertising planning processes in industries characterized by high uncertainty and risk